1964
DOI: 10.1111/j.1365-3032.1964.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Discharge and manipulation of labial gland secretion by workers of Apis mellifera (L.) (Hymenoptera: Apidae)

Abstract: SYNOPSISAn account is given of the salivation process in Apis mellifera. The mechanisms by which the hairs of the tongue are erected and the ligula retracted, and the action of the salivary pump, are described, and their effect on the discharge of saliva and intake of food are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The dynamic surface not only changes its surface configuration by unfolding the glossal hairs, but also elongates the segmented structures along the long axis of the tongue, which can further enhance the volume for nectar feeding. In this way, the tongue of a honey bee could derive the maximum amount of nutrients while being withdrawn, like a sponge that is alternately allowed to expand to take up water and squeezed to expel it (Simpson and Riedel 1964). According to the theoretical analysis, deformation of glossal surface can increase the thickness of adhered nectar through the combined action of viscosity and capillarity, which will benefit the honey bees' feeding efficiency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The dynamic surface not only changes its surface configuration by unfolding the glossal hairs, but also elongates the segmented structures along the long axis of the tongue, which can further enhance the volume for nectar feeding. In this way, the tongue of a honey bee could derive the maximum amount of nutrients while being withdrawn, like a sponge that is alternately allowed to expand to take up water and squeezed to expel it (Simpson and Riedel 1964). According to the theoretical analysis, deformation of glossal surface can increase the thickness of adhered nectar through the combined action of viscosity and capillarity, which will benefit the honey bees' feeding efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…The close consistency between the erection of glossal hairs and elongation of glossal segments indicates that the glossa of a honey bee is a highly-evolved and subtle mechanism. Driven by the muscles and an elastic glossal rod, the glossa can be elongated and compacted, with the glossal hairs erected and flattened synchronously, and the tiny membrane-structured glossal segments create possibilities for linking these two types of motions together (Simpson and Riedel 1964). The muscles slowly load the spring-like intersegmental membranes producing the erection of glossal hairs and elongation of segments and later the release of potential energy causes the flattening of hairs immediately.…”
Section: Discussionmentioning
confidence: 99%
“…In the interval, the tube retracts and the remaining nectar is sucked inside [Figs. 3(e)-3(g)]. A key step in acquiring nectar is to erect the hairs to trap water, as confirmed by Snodgrass 11 and Simpson and Riedel, 19 The video by Kim et al 15 shows the erection during the drinking process.…”
mentioning
confidence: 97%
“…In long-tongued bees, as in G. soricina, the hair-like projections are dynamic during nectar feeding. In bees, the bristles become erect when the tunic surrounding the tongue is stretched longitudinally during tongue protrusion (20), whereas we found that in G. soricina, the hair-like papillae are actively inflated by blood flow into the papillary veins. Although lapping behavior has not been studied in detail in the honey possum, these mammals also have enlarged blood vessels and a single midline artery in the tongue tip (21,22), suggesting that they may also hemodynamically inflate their lingual papillae.…”
Section: Discussionmentioning
confidence: 53%